Analisis Penerapan Prioritas Penggunaan Dana Desa Berdasarkan Permendesa PDTT di Desa Karangaji Kecamatan Kedung Kabupaten Jepara Pada Tahun 2016-2019 - Nor Arif; Fatchur Rohman (Jurnal Rekognisi Akuntansi, 2020)
This study aims to analyze the application of priority use of village funds based on the Permendesa PDTT in Karangaji Village, Kedung District, Jepara Regency in 2016-2019. This research is descriptive qualitative research using a case study model (Case Study). The data used are primary data (interview results) and secondary data (copy file of the Village Revenue and Expenditure Budget (APBDes) from Karangaji Village, Kedung District, Jepara Regency in 2016-2019). Informants from this study were the Village Head, Village Secretary, Head of Administrative and General Affairs, and Head of Financial Affairs. The data processing method used is data sorting, data classification, data editing, and data confirmation. The analytical method used in this research is the analytical technique by Miles & Huberman which starts from data collection, data reduction, data presentation to conclusion drawing, and data verification. The results of this study explain that the application of the Permendesa PDTT or the Regulation of the Minister of Villages for Disadvantaged Regions and Transmigration regarding the priority of using village funds can be said to have not been fully implemented, there are several obstacles related to the implementation of the priority use of village funds experienced by Karangaji Village to create some expectations regarding the achievement of priorities the use of village funds in Karangaji Village.